Making small states less vulnerable : supporting development during globalisation : a report (Commonwealth Secretariat LondonGB, 1999)
Presents the main findings of the Task Force on Small States. Explains the genesis of the Task Force and analyzes what is different about small states. Discusses the impact of globalization and what domestic policies are likely to be more effective in addressing structural and transitional problems. Proposes to the development community an approach towards small states based on partnerships, regionalism, openness to trade, integration with the international capital market, and careful consideration of transition issues - pacing and sequencing. Presents the World Bank strategy for small states.
Bibliography: p. 24-25